The influence of ideological education on students’ mental health during the pandemic: An empirical analysis based on big data and intelligent model - Liu, Lianxiang (Frontiers in Psychology, 2022)
Ideological education is an important part of students' education. Good ideological education can greatly reduce students' mental health problems. Based on relevant theories of psychology, this study analyzes that psychological crisis can be warned through continuous observation of emotions, and builds a psychological crisis warning model based on education big data, providing innovative observation methods and ideas for psychological crisis warning of college students. Stress events and the core idea of the model is that the personality of the mood change is internal and external cause, the calculation on the basis of the calculation of stress events and personality, can draw different types of emotions and emotional threshold intensity, to judge emotions, at the same time based on time sequence mood change to judge college students' psychological crisis faced by the level of risk. Combined with psychology knowledge and machine learning method, this study to improve mood, on the basis of prediction algorithm is proposed based on education data of psychological crisis early warning algorithm, this algorithm by calculating the personality, the influence of stress events and emotions calculation and attenuation to predict the duration and intensity, effectively avoid the pure probability problems by using machine learning algorithms. The simulation results show that the proposed algorithm can reflect the emotional changes of college students when they are subjected to stress events, and the effectiveness of the proposed algorithm is preliminarily verified. we conducted timely psychological intervention for the students who received negative stimuli, and the results show that timely psychological intervention and ideological education support are necessary and helpful.